Aktivitas Antibakteri dan Formulasi Krim Dari Ekstrak Etanol Daun Kemangi (Ocimum basilicum L.) dan Daun Kari (Murraya koenigii L.) - Safrina, Safrina; Novita, Eva; Mardhatillah, Mardhatillah; Syaddry, Alfi Yanna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The use of medicinal plants as active ingredients in topical formulations has been increasingly explored as a natural alternative to synthetic antimicrobial agents. This study aimed to formulate and evaluate a topical cream containing a combination of ethanolic extracts of curry leaves (Murraya koenigii L.) and basil leaves (Ocimum basilicum L.) as a natural antibacterial agent against Staphylococcus aureus. The extracts were prepared through maceration using 96% ethanol, followed by phytochemical screening and antibacterial testing using the well-diffusion method against Staphylococcus aureus ATCC 25923. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, phenolics, saponins, and steroids in both extracts. The antibacterial assay showed that the 1:1 extract combination produced an average inhibition zone of 14.17 mm, classified as strong and exhibiting a partial synergistic effect compared with single extracts. Several oil-in-water (O/W) cream formulations were then developed to determine optimal physical stability. Formula F2 (2:1) demonstrated the best physical stability, with pH 6 ± 0.1, spreadability of ±5 cm, adhesion time >140 seconds, and viscosity of 4500–5000 cP, all meeting the SNI 16-4399-1996 standard. These findings indicate that the 1:1 combination ratio provides the highest antibacterial activity, while the 2:1 ratio yields the most stable physical characteristics, suggesting that both can serve as the basis for developing a safe, stable, and effective natural topical antibacterial cream against Staphylococcus aureus.